Role of the transjugular intrahepatic portosystemic shunt in the management of severe complications of portal hypertension in idiopathic noncirrhotic portal hypertension. Issue 1 (13th May 2016) - Bissonnette, Julien; Garcia‐Pagán, Juan Carlos; Albillos, Agustín; Turon, Fanny; Ferreira, Carlos; Tellez, Luis; Nault, Jean‐Charles; Carbonell, Nicolas; Cervoni, Jean‐Paul; Abdel Rehim, Mohamed; Sibert, Annie; Bouchard, Louis; et al.
Abstract : Idiopathic noncirrhotic portal hypertension is a heterogeneous group of diseases characterized by portal hypertension in the absence of cirrhosis. The efficacy and safety of transjugular intrahepatic portosystemic shunt (TIPS) in this population are unknown. The charts of patients with idiopathic noncirrhotic portal hypertension undergoing TIPS in seven centers between 2000 and 2014 were retrospectively reviewed. Forty‐one patients were included. Indications for TIPS were recurrent variceal bleeding (n = 25) and refractory ascites (n = 16). Patients were categorized according to the presence (n = 27) or absence (n = 14) of significant extrahepatic comorbidities. Associated conditions were hematologic, prothrombotic, neoplastic, immune, and exposure to toxins. During follow‐up (mean 27 ± 29 months), variceal rebleeding occurred in 7/25 (28%), including three with early thrombosis of the stent. Post‐TIPS overt hepatic encephalopathy was present in 14 patients (34%). Eleven patients died, five due the liver disease or complications of the procedure and six because of the associated comorbidities. The procedure was complicated by hemoperitoneum in four patients (10%), which was fatal in one case. Serum creatinine ( P  = 0.005), ascites as indication for TIPS ( P  = 0.04), and the presence of significant comorbidities ( P  = 0.01) at the time of the procedure were associated with death. Mortality was higher in patients with significant comorbidities and creatinine ≥100 μmol/L ( P  < 0.001). Conclusion : In patients with idiopathic noncirrhotic portal hypertension who have normal kidney function or do not have severe extrahepatic conditions, TIPS is an excellent option to treat severe complications of portal hypertension. (Hepatology 2016;64:224–231)